Surface roughness profile and its effect on coating adhesion and corrosion protection: A review - Croll, S.G. (Progress in organic coatings, 2020)
•Surface roughness profile characteristics that affect adhesion and corrosion creep.•Why adhesion test results do not correlate with corrosion protection.•Surface profile factors affecting rate of corrosion creep.•Disciplines outside polymer coatings included in review. Specifications for coating many forms of infrastructure and equipment include abrasive cleaning, then measurement of the surface profile and adhesion on the assumption that they are linked to long term prevention of corrosion undercutting the coating. Studies find no quantitative connection between adhesion and corrosion protection, but many believe in a link. Although corrosion is a molecular phenomenon that starts at the interface, adhesion values are measured by a device attached to the coating at some distance from the interface, so it is difficult to directly connect corrosion with adhesion. Understanding how adhesion and the spread of corrosion under the coating are influenced by surface roughness entails surface metrology, fracture mechanics, surface energy and viscoelasticity. The impact of surface roughness cannot be not determined by a simple, or single, statistical parameter for variation in substrate height variation. Conventional “pull-off” adhesion testing does not characterize coating-metal interactions that might prevent water and electrolyte causing corrosion, they must be determined otherwise. The additional surface area created by the abrasion increases the number of adhesive interactions and the local slope of the surface engages Mode II loading that increases the force that the interface can support. Both these surface attributes may also slow the spread of corrosion across the interface. In order to prevent the diffusion of water and electrolyte across the interface, a coating should form well at the interface, be tough and as hydrophobic as realistically possible.